Rheo-NMR velocimetry of nanocrystalline cellulose suspensions - Stanley Maribelle A.; Jayaratne Jayesha S.; Codd Sarah L.; Bajwa Dilpreet S.; Wilking James N.; Seymour Joseph D. (Applied Rheology)
The velocity data presented demonstrate the complicated flow behavior of nanocrystalline cellulose (NCC) suspensions even when standard rheometry shows only subtle effects. Rheo-nuclear magnetic resonance (NMR) velocimetry with spatial and temporal resolution indicates that NCC suspensions undergo varying flow behavior, which correlates with bulk rheology and includes wall-slip, shear banding, and yielding. Large-velocity fluctuations in a chiral nematic liquid crystal-phase suspension (5% w/v) indicate particle director orientation tumbling and flow. The results provide details of the mesoscale velocity distributions in space and time, which can be used to inform the interpretation of rheology data, as well as processing flow conditions to control NCC suspension microstructure and impact properties of composite and other materials.